해안 단극성 와류의 거동 특성 - 최성은; 윤선민; 김열우; Choi, Seongeun; Yoon, Sunmin; Kim, Yeulwoo (Journal of Korea Water Resources Association, 2024)
This study utilizes a large eddy simulation technique to analyze the three-dimensional flow structures and turbulence characteristics of monopolar vortex generated by a long wave. Numerical simulations are validated with laboratory experiments conducted in a large scale three-dimensional wave tank at Oregon State University, comparing the trajectory of the vortex center and velocity fields. By incorporating an additional surface tension coefficient, a trend of increasing convergence in ensemble-azimuthal-averaged velocity components on the free surface is identified. The increased realization using an additional surface tension coefficient results in a reduced error for ensemble-azimuthal-averaged velocity and vorticity between the numerical simulations and the experimental data. The kinematic energy of vertical velocity component is found to be relatively lower than that in other directions, thus the monopolar vortex is considered to exhibit quasi-two-dimensional flow characteristics. Likewise, velocity spectra in the azimuthal direction shows isotropic eddies, while those in the vertical direction show a rapid dissipation slope, supporting the evidence of quasi-two-dimensional flow. The vertical distribution of turbulent kinetic energy shows a uniform profile, although that of turbulence production is non-uniform due to local shear and recirculation. The turbulence dissipation also shows a non-uniform vertical distribution influenced by bed shear stress. 본 연구에서는 장파에 의해 발생하는 단극성 와류의 삼차원 유동 구조와 난류 특성을 분석하기 위해 large eddy simulation 기법을 활용하였다. 오리건 주립 대학교의 삼차원 조파 수조에서 수행된 수리모형실험을 기반으로, 수치모형실험 결과를 와류 중심부의 이동 경로와 속도장과 비교하여 검증하였다. 표면장력 계수를 추가적으로 고려하면서 앙상블-방위각 평균된 자유수면 유속 성분의 수렴성이 시간이 지남에 따라 증가하는 경향을 보였다. 또한, 표면장력 계수의 증가로 앙상블-방위각 평균 유속이 수리모형실험과의 오차가 감소하면서, 추가적인 수치모형실험의 타당성이 입증 되었다. 각 방향에 따른 운동 에너지를 비교한 결과, 수심 방향 에너지가 다른 방향 에너지에 비해 상대적으로 작아, 단극성 와류 흐름이 준 이차원 흐름임을 나타낸다. 이와 같은 맥락에서, 방위각 속도 스펙트럼은 등방성을 유지하였으나 수심 방향 속도 스펙트럼은 더 높은 소산율 기울기를 나타내어 준 이차원 흐름 특징을 재확인하였다. 단극성 와류의 난류 에너지는 수심 방향으로 비교적 균일하나 국부 전단력과 재순환에 의해 난류 생성율의 수직 분포는 비균일하였으며, 난류 소산율 또한 수직 분포에서 국부 전단력의 영향으로 비균일성을 보였다.